The Knowledge Manager’s Role And Tasks For Supply Chain Management Success - De Giovanni, Pietro (Journal of Knowledge Management Practice, 2009)
This research addresses some emergent contradictions between theory and practice in recognizing Supply Chain (SC) manager’s position, role, and responsibilities. The analysis of numerous pieces of secondary information contained in a number of empirical studies reveals that the SC manager seldom drives SCs. Although all the analyzed articles address SC management issues, SC managers rarely provide the required information during the data collection phase. If the theory broadly recognizes SC manager, this early information shows his rare presence in practice. Driven by this result, the current research develops qualitative and quantitative investigations to clarify this divergence. The qualitative analysis uses structured interviews. One main result emerges: Knowledge Manager (KM) is the only one able to manage successfully SCs. As this statement is quite new in the SC management literature, the current research analyzes the KM’s roles and tasks and investigates his suitability for managing the entire SC. Moreover, it explores whether the firms’ success increases when KM manages SCs. This research unifies the fields of knowledge and SC management, underlines some divergences between theory and practice, and develops both qualitative and quantitative analyses to come up with reliable contributions.
Keywords: Supply chain; Knowledge manager; Knowledge management; Quantitative analysis; Qualitative analysis; Firm success